1997
DOI: 10.1007/s002689900235
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Acute Nonperforated and Perforated Appendicitis: Age‐specific and Sex‐specific Analysis

Abstract: This prospective study was performed to investigate epidemiological characteristics in terms of the age- and sex-specific incidence in patients with perforated and nonperforated appendicitis. The study population comprised 1486 consecutive patients who underwent appendectomy for suspected acute appendicitis between 1989 and 1993. Two patient cohorts [n = 544 (37%)] were analyzed with regard to prehospitalization duration of symptoms and in-hospital observation time. The crude incidence of acute appendicitis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
234
5
16

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(293 citation statements)
references
References 17 publications
26
234
5
16
Order By: Relevance
“…The association found between age and risk of PA is in agreement with previous studies 9,27 . The main reason for this increased risk has been suggested to be delayed diagnosis 28 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association found between age and risk of PA is in agreement with previous studies 9,27 . The main reason for this increased risk has been suggested to be delayed diagnosis 28 .…”
Section: Discussionsupporting
confidence: 93%
“…Perforation of the appendix occurs in 20-30 per cent of cases of acute appendicitis 4,8 and is associated with an increased risk of various complications. Perforated appendicitis (PA) occurs most frequently in children aged less than 5 years and in patients over 65 years old 9 . However, it has also been shown that the incidence of PA is independent of age 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis can be seen in all age groups whereas it commonly affects younger population in the second and third decades of life (11,12). As the global life expectancy increases and the population gets older, some disease may shift to elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Parte de la explicación a este fenómeno se encuentra en la heterogeneidad de los pacientes que se presentan en el grupo de probabilidad intermedia, por lo general, ancianos, inmunosuprimidos y mujeres en edad fértil (17,18). En especial, en este último grupo se ha reconocido que existe una tasa mayor de apendicectomías no terapéuticas (19)(20)(21)(22)(23), situación que ha motivado el uso rutinario de la ecografía y la tomografía abdominal (24,25) y de otros métodos diagnósticos, así como la recolección estructurada de datos (26). Esto sugiere que las mujeres en edad fértil y con hallazgos clínicos de dolor en la fosa ilíaca derecha, deben someterse a un período de observación más largo o a un escrutinio diagnóstico mucho más intenso, como se observa en el presente estudio.…”
Section: Discussionunclassified